2016
DOI: 10.2500/aap.2016.37.3910
|View full text |Cite
|
Sign up to set email alerts
|

Real-life effectiveness of budesonide/formoterol therapy in asthma: A subanalysis of the SMARTASIA study

Abstract: In China, asthma control in Chinese patients whose asthma was not fully controlled with previous standard therapy improved during 12 weeks of treatment with budesonide/formoterol maintenance and reliever therapy. Quality of life was improved, and treatment was well tolerated. (Clinical Trials identifier NCT00939341).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Lin et al 2 performed a 12-week, multicenter, open-label therapeutic phase IV study in which patients with partially controlled or uncontrolled asthma were switched from their usual asthma treatment to a budesonide/formoterol (160/4.5 g, one inhalation twice daily and as needed) regimen. The authors found that asthma control and quality of life improved in Chinese patients who received treatment with the budesonide/formoterol maintenance and reliever therapy.…”
mentioning
confidence: 99%
“…Lin et al 2 performed a 12-week, multicenter, open-label therapeutic phase IV study in which patients with partially controlled or uncontrolled asthma were switched from their usual asthma treatment to a budesonide/formoterol (160/4.5 g, one inhalation twice daily and as needed) regimen. The authors found that asthma control and quality of life improved in Chinese patients who received treatment with the budesonide/formoterol maintenance and reliever therapy.…”
mentioning
confidence: 99%